PENGEMBANGAN APLIKASI LAYANAN WISATA MENGGUNAKAN TOURGUIDE DI KOTA PADANG DENGAN PLATFORM ADROID - Ridho Nasser; Yasdinul Huda (Universitas Negeri Padang, 2019)
ABSTRACTTourism is one of the activities carried out by humans who have a purpose as entertainment. One of the objectives of designing this information system is to make tourist objects that have not been managed by the government to be managed and developed which makes it a source of income for the city of Padang. Padang City, the capital of West Sumatra Province, is one of the best tourism cities such as nature tourism, marine tourism and historical tourism. Natural attractions such as panoramas, waterfalls and natural baths, marine tourism such as beaches, while historical tourism such as monuments, and museums. However, due to lack of information, only a number of Padang City attractions are known by tourists. This system is built for two views, namely views for Web-based server pages, and views for android-based client pages using the android web view while system modeling uses UML (Unified Modeling Language). Then for the programming languages used are PHP, java and MySQL as Database..Keywords: Tourism, Tour Guide, UML, PHP, MySQL, Database, Tourism Objects, Padang City.